Kelayakan Buku Panduan Lapangan “Keanekaragaman Pohon di Lingkungan Kampus Universitas Lambung Mangkurat” sebagai Sumber Belajar Mandiri Konsep Keanekaragaman Hayati - Novia Andira; Noorhidayati Noorhidayati; Maulana Khalid Riefani (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2021)
The environment is a natural laboratory that presents unique phenomena that humans must study. Plants in the surrounding environment can be used as learning resources and media to bring students closer to their learning objects. Learning by utilizing objects in the surrounding environment can help the learning process. The diversity of tree in the Lambung Mangkurat University campus can be used as a source of learning and support learning based on the concept of diversity. One of the learning media that can be developed is a field guide book to guide users when learning independently in the environment. This study aims to describe the validity of the results of the development of a field guide "diversity of trees in the Lambung Mangkurat University campus". The feasibility of the field guide book was obtained from two experts and one high school biology teacher. The results of the validator's input and suggestions become material for correction and revision of learning products. The results of the field guide book validation show that the product is very valid and theoretically or procedurally feasible to be used for implementation at a later stage.